1994
DOI: 10.1111/j.1558-5646.1994.tb05304.x
|View full text |Cite
|
Sign up to set email alerts
|

EVIDENCE FOR RESTRICTED GENE FLOW IN THE VIVIPAROUS CORALSERIATOPORA HYSTRIX ONAUSTRALIA'S GREAT BARRIER REEF

Abstract: Abstract. -Viviparous, branching corals such as Seriatopora hystrix are expected to generate most recruits through asexual reproduction (fission or fragmentation) but are expected to use sexual reproduction to produce widely dispersed colonists. In this study, allozyme electrophoresis was used to test for variation in the relative contributions of sexual and asexual reproduction to recruitment and to assess the apparent scale of larval dispersal (gene flow) in the central Great Barrier Reef. Fifty-seven collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
48
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(66 citation statements)
references
References 48 publications
17
48
1
Order By: Relevance
“…Moreover, the levels of selfing detected in this study are consistent with previous reports of large heterozygote deficiencies in populations of S. hystrix from two other studies along the Great Barrier Reef (Ayre and Dufty, 1994; Ayre and Hughes, 2000). Heterozygote deficits are a common feature of many marine populations and are often presented as evidence in support of mating systems characterized by high levels of inbreeding and/or selfing (Ayre and Dufty, 1994;Edmands and Potts, 1997;Viard et al, 1997;Hughes, 2000, 2004;Reusch, 2001;Goffredo et al, 2004). Nevertheless, other potential factors may contribute to heterozygote deficits, for example, selection against heterozygotes (Borsa et al, 1992), the presence of null alleles (Foltz, 1986;Ayre et al, 1997), and the inadvertent sampling of multiple genetic subpopulations with differing allele frequencies (that is, the Wahlund effect, Hedrick, 2000).…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Moreover, the levels of selfing detected in this study are consistent with previous reports of large heterozygote deficiencies in populations of S. hystrix from two other studies along the Great Barrier Reef (Ayre and Dufty, 1994; Ayre and Hughes, 2000). Heterozygote deficits are a common feature of many marine populations and are often presented as evidence in support of mating systems characterized by high levels of inbreeding and/or selfing (Ayre and Dufty, 1994;Edmands and Potts, 1997;Viard et al, 1997;Hughes, 2000, 2004;Reusch, 2001;Goffredo et al, 2004). Nevertheless, other potential factors may contribute to heterozygote deficits, for example, selection against heterozygotes (Borsa et al, 1992), the presence of null alleles (Foltz, 1986;Ayre et al, 1997), and the inadvertent sampling of multiple genetic subpopulations with differing allele frequencies (that is, the Wahlund effect, Hedrick, 2000).…”
Section: Discussionsupporting
confidence: 81%
“…Previous population genetic studies of S. hystrix on the Great Barrier Reef have shown that certain allozyme loci are highly variable and provide a useful marker system to assess population structure and mating system in this species (for example, Ayre and Dufty, 1994;Ayre and Hughes, 2000). Tissue extracts and electrophoresis methods were the same as those described by Ayre and Dufty (1994).…”
Section: Electrophoresismentioning
confidence: 99%
See 2 more Smart Citations
“…Recent work on S. hystrix populations using highly variable microsatellite markers showed dispersal mostly occurred over small spatial scales (less than 100 m), although this was supplemented by less frequent longer-distance dispersal (Underwood et al 2007). Localized dispersal generally leads to high population differentiation, and earlier research on GBR S. hystrix populations (using allozymes) confirms this (F ST ¼ 0.43, Ayre & Dufty 1994; F ST ¼ 0.15, Ayre & Hughes 2000). Despite the usually rapid settlement of larvae, some brooding corals produce a small proportion of larvae that have extended competency periods of over 100 days in the water column (e.g.…”
Section: Introductionsupporting
confidence: 61%